Super-enhancer-based identification of a BATF3/IL-2R-module reveals vulnerabilities in anaplastic large cell lymphoma - Liang, Huan-Chang; Costanza, Mariantonia; Prutsch, Nicole; Zimmerman, Mark W; Gurnhofer, Elisabeth; Montes-Mojarro, Ivonne A; Abraham, Brian J; Prokoph, Nina; Stoiber, Stefan; Tangermann, Simone; Lobello, Cosimo; Oppelt, Jan; et al. (Nature communications, 2021)
Anaplastic large cell lymphoma (ALCL), an aggressive CD30-positive T-cell lymphoma, comprises systemic anaplastic lymphoma kinase (ALK)-positive, and ALK-negative, primary cutaneous and breast implant-associated ALCL. Prognosis of some ALCL subgroups is still unsatisfactory, and already in second line effective treatment options are lacking. To identify genes defining ALCL cell state and dependencies, we here characterize super-enhancer regions by genome-wide H3K27ac ChIP-seq. In addition to known ALCL key regulators, the AP-1-member BATF3 and IL-2 receptor (IL2R)-components are among the top hits. Specific and high-level IL2R expression in ALCL correlates with BATF3 expression. Confirming a regulatory link, IL-2R-expression decreases following BATF3 knockout, and BATF3 is recruited to IL2R regulatory regions. Functionally, IL-2, IL-15 and Neo-2/15, a hyper-stable IL-2/IL-15 mimic, accelerate ALCL growth and activate STAT1, STAT5 and ERK1/2. In line, strong IL-2Rα-expression in ALCL patients is linked to more aggressive clinical presentation. Finally, an IL-2Rα-targeting antibody-drug conjugate efficiently kills ALCL cells in vitro and in vivo. Our results highlight the importance of the BATF3/IL-2R-module for ALCL biology and identify IL-2Rα-targeting as a promising treatment strategy for ALCL.
Keywords: anaplastický velkobuněčný lymfom; receptor interleukinu-2 - alfa-podjednotka; Gene Expression Regulation, Neoplastic; regulační oblasti nukleových kyselin; antigen Ki-1; Lymphoma, Large-Cell, Anaplastic; viabilita buněk; represorové proteiny; imunokonjugáty; Cell Line, Tumor; Cell Proliferation; receptory interleukinu-2; Interleukin-2; transkripční faktory bZIP; Xenograft Model Antitumor Assays; regulace genové exprese u nádorů; signální transdukce; Cell Survival; Interleukin-15; Basic-Leucine Zipper Transcription Factors; Signal Transduction; xenogenní modely - testy protinádorové aktivity; Animals; lidé; interleukin-2; Ki-1 Antigen; Humans; interleukin-15; zvířata; Receptors, Interleukin-2; myši; Regulatory Sequences, Nucleic Acid; Repressor Proteins; proliferace buněk; Interleukin-2 Receptor alpha Subunit; nádorové buněčné linie; Mice; Immunoconjugates